'Half Man, Half Chair': Disability and the Posthuman Technological Imaginaries of Miserrimus Dexter's Sensational Body in Wilkie Collins' The Law and the Lady (1875). (September 2022) - Reilly, Esther
Abstract : Questions of identity are central to Wilkie Collins' 1875 novel, The Law and the Lady, where we find the extraordinary and androgynous body of wheelchair-using Miserrimus Dexter. Disabled and without legs since birth, and described as 'the new Centaur, half-man, half-chair, ' Dexter's disfigured body is one of Collins' most shocking and confusing characters. As a fusion of man and machinery, Dexter is even more extreme than Collins' many other sensational characters and fascinating because of his exaggerated physical difference, eccentric behaviour, and hybrid identity. Dexter is represented as a hybrid, a bizarre mix of the human, non-human animal, and machine. He is a unique example of Collins' sensational ability to draw on social fears and anxieties by creating an extreme body that is capable of crossing 'natural' boundaries, propelling Dexter towards what we now know as 'posthumanism.' This essay examines how the sensation genre allows Collins to test out freakish/posthuman/cyborg bodies. Dexter's physical limitations are overcome by uniting his body with technology. However, as his identity becomes completely bound up with the mechanism he uses to move about, Collins depicts him becoming less human and increasingly unhinged. Collins' novel expresses anxieties about the dehumanising impact of the rise of technology rather than enthusiasm for the transhuman possibilities offered.